Effectiveness of Bee Venom Injection for Parkinson’s Disease: A Systematic Review - Hyein Jeong; Kyeong Han Kim; Seong-gyu Ko (Toxins)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder worldwide, affecting over 8.5 million people as of 2019. While standard pharmacological treatments help alleviate symptoms, their long-term use can lead to side effects such as dyskinesia. Bee venom acupuncture (BVA) involves the use of a natural toxin derived from bees that can be used for pain relief and treating neurological disorders. This study aimed to review the efficacy and safety of BVA for the treatment of PD. This review protocol was prospectively registered with PROSPERO (CRD420251000577). We searched eight databases in February 2025 and selected 12 studies involving 215 PD patients treated with BVA. Idiopathic Parkinson’s disease (IPD) is the most common diagnosis. The concentration and dosage per session ranged from 0.03 to 0.1 mg/mL and from 0.1 to 1.0 mL, respectively. Twenty-four different outcome measures were used, with the Unified PD Rating Scale employed in 91.7% of the studies. All studies reported improvements in outcomes. Mild adverse effects such as swelling and itching were noted in four studies (33.3%); however, no severe reactions such as anaphylactic shock occurred. These findings suggest that BVA has the potential for broader clinical applications in the treatment of PD.